WACANA PENCALONAN PRESIDEN DAN WAKIL PRESIDEN DARI JALUR INDEPENDEN DI INDONESIA - Putri Oktaviani; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aims to look at the discourse of the nomination of president and vice president of the independent public mistrust caused by the performance of political parties. Other than are the focus of this research is the discourse of the president of an independent could not be implemented in Indonesia because in the counstitution in 1945 of Article 6A paragraph (2) that the pair of candidates for president and vice president nominated by political parties or coalition of political parties participating in elections before general elections. But contrary to constitusional rights in law and government and shall abide by the law and the government is no exception and section 28D (3) that every citizen has the rights to obtain equal opportunities in government. This study is a research library. In this study used a qualitative approach with descriptive methods. Qualitative research is descriptive research and tend to use the analysis and based on the theoretical basis of research as aguide. One the things that need to be done in preparation of the study is to efficiently utilize information sources available in the use of library materials needed both for research documents (secondary data).Research shows that the discourse of the nomination of president and vice president of independent Indonesia can not be implemented, because it must be held of amendment constitution in 1945 to Article 6A paragraph (2) that the pair of candidates for president and vice president nominated by political parties or coalition of political parties participating in elections before implementation elections and make changes by adding the individual words in the article that is implemented in Indonesia.Keyword: Discourse, Nomination, Independent